Accidental Intrathecal Tranexamic Acid Injection During Caesarean Section: A Case Report - Raymond Oyugi Samuel; Victoria Adonicam; Andrew Hans Mgaya (Case Reports in Anesthesiology)
Conclusion: Medication error such as accidental intrathecal injection of TXA continues to jeopardise the safety of surgery under spinal anaesthesia.